Implementasi Metode Dempster Shafer Berbasis Web untuk Mendiagnosa Kerusakan Jaringan LAN - Sukmawati Sukmawati; Rifky Maulana; Ranti Holiyanti; Betha Nurina Sari (Universitas Indraprasta PGRI Jakarta, 2022)
Local Area Network (LAN) is a type of computer network that covers a local area and is widely used in various aspects.In places that provide LAN connections there are those using Wi-Fi technology which are usually called hotspots. Damage to the LAN, especially Wi-fi itself, is often experienced by the community.It is also inconvenient for internet network users due to lack of knowledge about the damage. Therefore, it is necessary to create a system that can be used to collect knowledge data from network experts and store it. The result of this research is an expert system that diagnoses LAN network damage. The system automatically provides diagnostic results by displaying the type of glitch and its solution based on the symptoms of the glitches experienced. The conclusion of this study is that an expert system by using the Dempster Shafer method to handle data uncertainty when diagnosing LAN service disruptions is very helpful in overcoming the problem of declining service quality.